Congenital Beckers nevus overlying plexiform neurofibroma in neurofibromatosis type-1: more than a rare association - Ramanand, Chetana Peenya; Balawat, Aishwarya; Shivaswamy, Kanakpura Nanjundaswamy; Sumathy, Tharayil Kunneth (International Journal of Research in Dermatology, 2025)
Plexiform neurofibroma (PFN) is the hallmark of Neurofibromatosis type 1 (NF-1), an autosomal dominant disorder caused by mutations in the neurofibromin gene.1 Becker’s nevus (BN) is an acquired pigmentary disorder characterized by hyperpigmentation and hypertrichosis, presenting in adolescence.2 Here we present a 28-year-old male with a congenital hyperpigmented pigmented patch over his back which later on increased in size and developed excessive hair growth and subsequently swelling. The patient had no other swellings of neurofibroma but satisfied all the criteria of Type-1 Neurofibromatosis. Clinical, dermoscopic and histopathologic features confirmed the diagnosis of PFN with BN in NF-1. Two special stains including S-100 and Fontana Mason stain ruled out other possibilities and further confirmed the diagnosis of Congenital Becker’s Nevus with Plexiform Neurofibroma in NF-1. The report emphasizes that in NF-1, Becker’s nevus can masquerade an ominous presence of plexiform neurofibroma. The case has been reported for the rarity of association of Congenital Beckers Nevus with Plexiform Neurofibroma in NF-1.